Impact of Allogeneic Hematopoietic Stem Cell Transplantation on the HIV Reservoir and Immune Response in 3 HIV-Infected Individuals. (1st July 2017) - Koelsch, Kersten K.; Rasmussen, Thomas A.; Hey-Nguyen, William J.; Pearson, Chester; Xu, Yin; Bailey, Michelle; Marks, Katherine H.; Sasson, Sarah C.; Taylor, Mark S.; Tantau, Robyn; Obeid, Solange; Milner, Brad; et al.
Abstract : Background: Allogeneic hematopoietic stem cell transplantation (HSCT) can lead to significant changes to the HIV reservoir and HIV immune responses, indicating that further characterization of HIV-infected patients undergoing HSCT is warranted. Methods: We studied 3 patients who underwent HSCT after either reduced intensity conditioning or myeloablative conditioning regimen. We measured HIV antigens and antibodies (Ag/Ab), HIV-specific CD4 + T-cell responses, HIV RNA, and DNA in plasma, peripheral blood mononuclear cells, isolated CD4 + T cells from peripheral blood, and lymph node cells. The patients remained on antiretroviral therapy throughout the follow-up period. Results: All patients have been in continued remission for 4–6 years post-HSCT. Analyses of HIV RNA and DNA levels showed substantial reductions in HIV reservoir–related measurements in all 3 patients, changes in immune response varied with pronounced reductions in 2 patients and a less dramatic reduction in 1 patient. One patient experienced unexpected viral rebound 4 years after HSCT. Conclusions: These 3 cases highlight the substantial changes to the HIV reservoir and the HIV immune response in patients undergoing allogeneic HSCT. The viral rebound observed in 1 patient indicates that replication competent HIV can re-emerge several years after HSCT despite these marked changes. Abstract : Supplemental Digital Content is Available in the Text.